Valve replacement in patients with critical aortic stenosis and depressed left ventricular function: predictors of operative risk, left ventricular function recovery, and long term outcome. Issue 10 (14th September 2005) - Vaquette, B; Corbineau, H; Laurent, M; Lelong, B; Langanay, T; de Place, C; Froger-Bompas, C; Leclercq, C; Daubert, C; Leguerrier, A
Abstract : Objectives: To identify predictors of operative and postoperative mortality and of functional reversibility after aortic valve replacement (AVR) in patients with aortic stenosis (AS) and severe left ventricular (LV) systolic dysfunction. Methods and results: Between 1990 and 2000, 155 consecutive patients (mean (SD) age 72 (9) years) in New York Heart Association (NYHA) heart failure functional class III or IV (n = 138) and with LV ejection fraction (LVEF) ⩽ 30% underwent AVR for critical AS (mean (SD) valve area index 0.35 (0.09) cm 2 /m 2 ). Thirty day mortality was 12%. NYHA class (3.7 (0.6) v 3.2 (0.7), p = 0.004), cardiothoracic ratio (CTR) (0.63 (0.07) v 0.56 (0.06), p < 0.0001), pulmonary artery systolic pressure (63 (25) v 50 (19) mm Hg, p = 0.03), and prevalence of complete left bundle branch block (22% v 8%, p = 0.03) and of renal insufficiency (p = 0.001) were significantly higher in 18 non-survivors than in 137 survivors. In multivariate analysis, the only independent predictor of operative mortality was a CTR ⩾ 0.6 (odds ratio (OR) 12.2, 95% confidence interval (CI) 5.4 to 27.4, p = 0.002). The difference between preoperative and immediate postoperative LVEF (early-ΔEF) was > 10 ejection fraction units (EFU) in 55 survivors. In multivariate analysis, CTR (OR 5.95, 95% CI 3.0 to 11.6, p = 0.006) and mean transaortic gradient (OR 1.05, 95% CI 1.0 to 1.1, p < 0.05) were independent predictors of an early-ΔEF > 10 EFU. During a mean (SD) follow up of 4.6 (3) years, 50 of 137 (36%) 30 day survivors died, 31 of non-cardiac causes. Diabetes (OR 3.8, 95% CI 2.4 to 6.0, p = 0.003), age ⩾ 75 years (OR 2.6, 95% CI 2.1 to 4.5, p = 0.004), and early-ΔEF ⩽ 10 EFU (OR 0.96, 95% CI 0.94 to 0.97, p = 0.01) were independent predictors of long term mortality. Among 127 survivors, the percentage of patients in NYHA functional class III or IV decreased from 89% preoperatively to 3% at one year. The decrease in functional class was significantly greater in patients with an early-ΔEF > 10 EFU than patients with an early-ΔEF ⩽ 10 EFU (p = 0.02). In addition, the mean (SD) LVEF at one year was 53 (11)% in patients with an early-ΔEF > 10 EFU and 42 (11)% in patients with early-ΔEF ⩽ 10 EFU (p < 0.001). Conclusions: Despite a relatively high operative mortality, AVR for AS and severely depressed LVEF was beneficial in the majority of patients. Early postoperative recovery of LV function was associated with significantly greater relief of symptoms and longer survival.